Importance of the Maintenance Pathway in the Regulation of the Activity of Escherichia coli Ribonucleotide Reductase† - Hristova, Daniela (American Chemical Society, 2008)
[Image: see text] Ribonucleotide reductases (RNRs) catalyze the conversion of nucleotides to deoxynucleotides in all organisms. The Escherichia coli class Ia RNR is composed of α and β subunits that form an α(2)β(2) active complex. β contains the diferric tyrosyl radical (Y(•)) cofactor that is essential for the reduction process that occurs on α. [Y(•)] in vitro is proportional to RNR activity, and its regulation in vivo potentially represents a mechanism for controlling RNR activity. To examine this thesis, N- and C-terminal StrepII-tagged β under the control of an l-arabinose promoter were constructed. Using these constructs and with [l-arabinose] varying from 0 to 0.5 mM in the growth medium, [β] could be varied from 4 to 3300 µM. [Y(•)] in vivo and on affinity-purified Strep-β in vitro was determined by EPR spectroscopy and Western analysis. In both cases, there was 0.1–0.3 Y(•) radical per β. To determine if the substoichiometric Y(•) level was associated with apo β or diferric β, titrations of crude cell extracts from these growths were carried out with reduced YfaE, a 2Fe2S ferredoxin involved in cofactor maintenance and assembly. Each titration, followed by addition of O(2) to assemble the cofactor and EPR analysis to quantitate Y(•), revealed that β is completely loaded with a diferric cluster even when its concentration in vivo is 244 µM. These titrations, furthermore, resulted in 1 Y(•) radical per β, the highest levels reported. Whole cell Mössbauer analysis on cells induced with 0.5 mM arabinose supports high iron loading in β. These results suggest that modulation of the level of Y(•) in vivo in E. coli is a mechanism of regulating RNR activity.